Managed forest as habitat for gray brocket deer (Mazama gouazoubira) in agricultural landscapes of southeastern Brazil - Rodrigues, Thiago Ferreira; Kays, Roland; Parsons, Arielle; Versiani, Natalia Fraguas; Paolino, Roberta Montanheiro; Pasqualotto, Nielson; Krepschi, Victor Gasperotto [UNESP]; Chiarello, Adriano Garcia (Oxford Univ Press Inc, 2017)
Because of massive conversion of natural habitat into cropland, the future of many tropical mammals depends on understanding how agricultural landscapes influence biodiversity. We assessed the effects of natural and anthropogenic land covers and disturbances on occupancy of gray brocket deer (Mazama gouazoubira) in 3 agricultural landscapes in the Brazilian Cerrado where sugarcane or managed forest cover most (> 50%) of the landscape. We used camera-trap surveys to quantify the relationships between deer occurrence and land cover, unpaved roads, urban areas, waterways, and degrees of legal protection. We found a strong and positive effect of managed forests, indicating that this land cover is good habitat for the brocket deer in our region. Native forests and sugarcane had, surprisingly, weaker effects on deer occupancy. Furthermore, the effect of sugarcane varied according to the amount of remaining natural forest: when the amount of natural forest surrounding the camera point was scarce, sugarcane had a negative effect on deer occupancy, but the effect was positive when natural forest was abundant. Our results confirm the ecological flexibility of gray brocket deer, even in landscapes where sugarcane monocultures or Eucalyptus plantations predominate. We caution however that the responses of deer might be different in landscapes more severely depleted of natural vegetation (< 20% at the landscape level). We therefore suggest that future research assess the population status of this deer in more deforested landscapes, and also consider the temporal dynamics of managed forests and sugarcane, as the vegetation cover can change drastically.
Keywords: camera trapping; Cerrado; herbivores; land use; occupancy